The description of characteristics of mothers with child care at Muthia Daycare Center Sleman Yogyakarta - Nurul Kurniati (International Journal of Health Science and Technology, 2022)
Infancy and toddlerhood are an important period in child development. So, in providing high-quality and comprehensive care for infants and toddlers, it is very important for parents to know the development of infants and toddlers as a basis for knowing further developments, namely pre-school, school, puberty and adolescence. Parents, especially mothers, must have knowledge about the development process in pre-school age children so that if there are developmental abnormalities, they can be detected early. The purpose of this study was to determine the characteristics of mothers with child care at Muthia Daycare Sleman. This study used a cross sectional approach with quantitative research. The samples used by the quota sampling method were all mothers who cared for their toddlers at Muthia Daycare Sleman (TPA) as many as 30 mothers. Collecting data with a questionnaire then the data was processed and descriptive analysis was carried out with a computer system. The results showed that most of the respondents were mothers with college education, namely 21 mothers (70%), most of them were of reproductive age, as many as 20 mothers (66.7%) in the age range of 30-40 years, most had attended seminars or training on parenting or growth and development of toddlers as many as 16 (53.3%), the need for information and education that was more needed by mothers related to gross motor skills of toddlers was 10 mothers (33.3%). The main suggestion is the need for stakeholder cooperation in an effort to increase mothers' understanding of the growth and development of toddlers, especially the existence of communication between parenting schools and parents so that the growth and development of toddlers is optimal.